ANALISIS FAKTOR-FAKTOR KESUKSESAN IMPLIKASI BSC YANG MEMPENGARAUHI KINERJA RUMAH SAKIT SENTRA MEDIKA CIKARANG TAHUN 2013 - Tutik Rahayu; Ediyanto (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
This research aimed to analyze nine key factors that influence BSC implementation for hospital performance. Census method used to sampling hospital managers, started from shift commander to superintendent of hospital. Multiple regression used as tools of analyzing to analyze ten hypothesis. Research was done at Sentra Medika Hospital Cikarang Branch. Conclusion from this research found seven from nine factors has great signification influence to hospital performance, they are officer and middle manager participation factor, culture of work factor, education and training factor, simple planning of BSC factor, sharpness of vision, strategy and result, incentive effect factor, and internal BSC team factor. Two others has no signification to hospital performance, they are top management supporting factor and resources factor.